Managing football infrastructure objects after World Cup 2018: foreign experience and Russian perspectives - Sh. M. Ramazanov (Управление)
In the article managerial and financial aspects of holding FIFA (фр. Fеdеration Internationale de Football Association) World Cup 2018 in Russia are disclosed. Foreign experience was analyzed, in particular, outstanding characteristics of holding FIFA World Cups in Brazil 2014. While having prepared for the World Cup 2014, Brazil spent almost 3 bln USD on building new stadiums and restructuring of existing ones. However, no attention was paid to remoteness of the arenas to popular football clubs’ locations, which led to serious problems with match - attendance and huge financial loses. Based on the analysis of Russian experience the need of complex approach to management of sports infrastructure objects as well as the development of a long-term development program on the part of federal and municipal regulatory bodies was identified and justified. This document is expected to reflect specific economic and legislative guidelines of stand-alone governmental structures. On the ground of the carried out survey, potential directions of subsequent utilization of sports infrastructure objects were formulated by the author which should be included into three groups. Sports-oriented exploitation implicates direct use of the objects in the capacity of arenas for conducting football matches and other competitions as well as other sports competitions (for instance, hockey, basketball, boxing and others). Commercial use supposes lease of territories and premises of the stadium. Culturally recreational use is about holding exhibitions, concerts, forums and conferences as well as citywide festivals, corporate and public events. Combination of mentioned above variants of use is possible.